Mechanism of Tongxie Yaofang in the treatment of colorectal cancer based on network pharmacology and molecular docking - Ling-Xia Yang (Editorial Board of Journal of Hainan Medical University, 2021)
Objective: To predict the mechanism of Tongxie Yaofang in the treatment of colorectal cancer (CRC). Methods: The active compounds and targets of Tongxie Yaofang were screened by the TCMSP database, and the MalaCards database used “Colorectal cancer” as the key word to search for CRC targets. After the two database were mapped, the overlapping targets are merged. In David 6.8 database, the GO function and KEGG pathway of intersection targets were analyzed. Cytoscape 3.7.2 was used to construct the networks of “Active compounds- Targets” and “Herbs-Active compounds-CRC-Targets”, and the core compounds and the key targets of Tongxie Yaofang in treating CRC were selected through Network Analysis. THE HUMAN PROTEIN ATLAS database was used to verify the protein expression of key genes. Using AutoDock Vina and Python scripts, the core compounds are interfaced with the key target protein receptors. Results: TCMSP database indicated that there were 34 active compounds and 114 targets of Tongxie Yaofang, while MalaCards database indicated that there were 838 targets closely related to CRC, and 52 cross targets were obtained from the two database. Go enrichment analysis showed that 1410 items were involved in the cross targets (P < 0.05) , and the biological process (BP) was mainly concentrated in Lipid metabolism, hormone reaction, proliferation and apoptosis of cancer cells; Cell composition (CC) mainly affected the mitochondrial membrane potential and endoplasmic reticulum stress of CRC cells; while Molecular Function (MF) mainly involves oxidoreductase activity, protein kinase activity, etc. KEGG pathway enrichment analysis indicated that 104 signaling pathways were involved in the cross targets (P < 0.05) including PI3K/Akt, TNF, TLR and so on. THE HUMAN PROTEIN ATLAS database showed that PTGS2, PTGS1, and ESR1 showed stronger positive protein expression in CRC tissues than normal intestinal tissues. The combination of Wogonin, Kaempferol and beta-sitosterol with PTGS2, PTGS1 and ESR1 were lower than ≤ −5.0 kJ/mol that showing good affinity. Conclusion: The Tongxie Yaofang in treating CRC involves many signal pathways and biological processes, and the main active components including Wogonin, Kaempferol, beta-sitosterol, and the key targets PTGS2, PTGS1, ESR1, may be one of the important mechanisms.